1994
DOI: 10.1002/ana.410360611
|View full text |Cite
|
Sign up to set email alerts
|

Manganese intoxication and chronic liver failure

Abstract: Manganese intoxication and chronic liver failure are associated with strikingly similar clinical, imaging, and pathological abnormalities. As manganese is primarily cleared by the liver, inadequate elimination of manganese absorbed from the normal diet may lead to manganese overload in patients with liver disease. We report a significant elevation of blood manganese concentration in 3 patients with biopsy-proved hepatic cirrhosis who exhibited neurological dysfunction and characteristic abnormal signal hyperin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(140 citation statements)
references
References 30 publications
10
129
0
1
Order By: Relevance
“…Previous studies [6][7][8]22) have shown that subjective MR imaging scores correlated with blood Mn concentrations. The present study confirmed and extended previous reports showing a correlation between increased pallidal signals and blood Mn concentrations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies [6][7][8]22) have shown that subjective MR imaging scores correlated with blood Mn concentrations. The present study confirmed and extended previous reports showing a correlation between increased pallidal signals and blood Mn concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…A similar MRI pattern has been observed in patients receiving total parenteral nutrition, because of excessive Mn intake 4,5) . Chronic liver failure is also associated with increased signal intensities in the GP using T1-weighted MRI 6,7) . The correlation between the MRI abnormalities in the GP and circulating Mn concentrations of cirrhotic patients suggests that the high signals are due to the paramagnetic Mn [8][9][10] .…”
mentioning
confidence: 99%
“…The pattern of MRI abnormalities resembles that of manganese overload. Patients with liver cirrhosis and high signal intensity in the globus pallidus on T1WI have higher blood manganese concentrations than healthy volunteers [40]. The hyperintense globus pallidus on T1WI seen in patients with chronic hepatic failure due to Alagille syndrome diminished 3 months after hepatic transplantation.…”
Section: Manganesementioning
confidence: 89%
“…An increased T1-weighted Mn signal in the globus pallidus area has been found among workers occupationally exposed to Mn (Dietz et al, 2001;Kim et al, 1999b;Lucchini et al, 2000;Nelson et al, 1993), in patients receiving long-term total parenteral nutrition (Alves et al, 1997;Ejima et al, 1992;Fell et al, 1996;Fredstrom et al, 1995;Iwase et al, 2000;Komaki et al, 1999;Nagatomo et al, 1999;Quaghebeur et al, 1996), and in clinical cases reported with hepatic failure (Butterworth et al, 1995;Chetri and Choudhuri, 2003;Hauser et al, 1994;Hazell and Butterworth, 1999;McKinney et al, 2004;Spahr et al, 2002). While in animal models the MRI intensity has been linked to external Mn exposure (Eriksson et al, 1992;Kim et al, 1999a;Misselwitz et al, 1995;Newland et al, 1989a,b;Shinotoh et al, 1995), the question as to how the change in MRI signals in humans is associated with external exposure conditions and whether this consequentially leads to alternations of the internal Mn exposure indices or the fluctuation in blood chemistry remains elusive.…”
Section: Introductionmentioning
confidence: 98%